Languages and the Military
XII, 249 p.
Keywords: Through detailed case studies ranging from the 18th century until today,this book explores the role of foreign languages in military alliances, in occupation and in peace building. It brings together academic researchers and practitioners from the museum and interpreting worlds and the military.